Psychosocial factors associated with depression severity in pregnant adolescents - Tzilos, Golfo K. (2012)
Adolescent depression during pregnancy is associated with increased morbidity for the teen and her infant. This cross-sectional study explored the relationships among the independent histories of alcohol use, drug use, depression, and abuse (physical or sexual) on depression severity in a diverse group of 116 pregnant adolescents (mean age=16) who attended an urban prenatal clinic. Ever having had an alcoholic drink was a significant predictor of higher depressive scores on Children's Depression Rating Scale-Revised, β=3.3 (0.8, 5.7); p<0.05. History of abuse was associated with a significant 4.3-point higher mean depressive score, β=4.3 (1.8, 6.7), p<0.001, and remained a statistically significant predictor of more severe depressive symptoms after adjustment for history of alcohol use, history of drug use, and history of depression. This study identified that a history of physical or sexual abuse is a significant factor related to the severity of depressive symptoms in pregnant adolescents, independent of a history of alcohol, drug use, or depression. These findings suggest that an assessment of history of alcohol use, as well as abuse history, may increase the likelihood of identifying adolescents at risk for antenatal depression.